Who move to rural areas' Micro Evidence from Finland - Satu Nivalainen (European Regional Science Association (ERSA), 2003)
This study uses a large individual-level dataset to investigate rural in-migration. Two separate samples are used: one consists of migrants and non-migrants, while the other contains only migrants. Empirical analyses are carried out using multinomial logit and logit models. First, rural in-migrants and non-migrants are compared. The results show that in-migration to rural areas is selective, but partly in an atypical way. The age profile of rural in-migrants is unusual, as the probability of migration increases with age. Furthermore, a typical rural in-migrant is a pensioner and has a smaller than average income. It is also notable that, with respect to educational level or family relations, rural in-migrants do not differ from non-migrants. Space and related housing factors seem to be of importance in rural in-migration decisions. The study also examines differences between rural in-migrants and other migrants. In general, those moving to rural areas are older, have a lower educational level and a smaller income. Pensioners, couples and families with children are also more likely move to rural regions. However, differences emerge in relation to the distance of migration: short distance rural in-migrants are more likely to be couples with young children, while long distance rural in-migrants are more often pensioners and return-migrants.
Keywords: 330